Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1471-2318-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Snoezelen, structured reminiscence therapy and 10-minutes activation in long term care residents with dementia (WISDE): study protocol of a cluster randomized controlled trial

Abstract: BackgroundPeople with dementia are often inapproachable due to symptoms of their illness. Therefore nurses should establish relationships with dementia patients via their remaining resources and facilitate communication. In order to achieve this, different targeted non-pharmacological interventions are recommended and practiced. However there is no sufficient evidence about the efficacy of most of these interventions. A number of publications highlight the urgent need for methodological sound studies so that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…None of these articles gave more explicit information about the pre-study diagnostic procedure or about whether an existing diagnosis was confirmed by the attending physician. In 14 articles, neither the definition of dementia and/or its diagnostic criteria were reported; in addition, no information was provided about the diagnostic procedure that had been undertaken prior to the study [ 42 45 , 47 , 82 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these articles gave more explicit information about the pre-study diagnostic procedure or about whether an existing diagnosis was confirmed by the attending physician. In 14 articles, neither the definition of dementia and/or its diagnostic criteria were reported; in addition, no information was provided about the diagnostic procedure that had been undertaken prior to the study [ 42 45 , 47 , 82 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 17 articles, it was reported that in addition to the recorded diagnosis or performed screenings, exclusion criteria were also used in the study [ 48 51 , 53 , 76 80 , 82 , 85 90 ]. These comprised other neurological or psychiatric diseases that could cause CI.…”
Section: Resultsmentioning
confidence: 99%
“…This process allows synthesizing the contributions and challenges arising from its multiple phases. With regard to Phase I (preliminary development), in order to identify the strengths and limitations of existing programs, a body of emerging evidence based on primary studies and systematic literature reviews (Berg et al, 2010;Stinson, 2009) were analyzed, with and without meta-analysis. This analysis confirmed the therapeutic potential of RT for the promotion of mental health among older people.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Gonçalves (2006) focused on older people with depressive symptoms, and Lopes, Afonso, and Ribeiro (2013) used individual interventions based on spontaneous memories. However, since none of these studies used standardized RT programs, research in this area calls for the development of a well--structured and replicable program (Berg et al, 2010;Stinson, 2009). In view of the above, the guidelines and recommendations of the Medical Research Council (Craig et al, 2008) for the development of complex interventions were followed to develop and validate an RT program to be applied to older people with cognitive impairment in institutional settings.…”
Section: Introductionmentioning
confidence: 99%
“…O local de seleção da amostra do estudo geralmente era em casas de repouso, intervindo com pessoas que estavam em diferentes estágios da demência, podendo ter ou não um grupo controle ou outra abordagem não farmacológica (ANDERSON et al, 2011;BAILLY;POINTEREAU, 2011;BAUER et al, 2012BAUER et al, , 2015BERG et al, 2010;COLLIER et al, 2010;CRUZ et al, 2013;KLAGES et al 2011;MARQUES et al, 2013;MASEDA et al, 2014b;SANCHEZ et al, 2013). Esses estudos também diferiram quanto ao desenho metodológico (tamanho amostral, protocolos de avaliação utilizados e estruturação das sessões -duração, frequência e tempo de permanência na sala) e efeitos a longo prazo não eram conclusivos, sendo recomendados estudos futuros (MACHADO et al, 2016).…”
Section: Variáveis Interferentesunclassified